EVALUATION TO ADAPTATION OF MOTHERHOOD IN POSTPARTUM PERIOD - Ozturk, Melike; Surucu, Sule Gokyildiz; Ozel, Tugce Esra; Inci, Halide (LIFE: International Journal of Health and Life-Sciences, 2017)
The purpose of this study was to examine women’s adaptation to motherhood and factors associated with adaptation to role of motherhood in the postpartum period. This research was a descriptive study. Study population included 125 women who were in the postpartum period of 30-40th day in Adana-Turkey. Data collection took place at three family medicine centers between February 2016-March 2016. Data were collected using a demographic questionnaire and Postpartum Self Evaluation Questionnaire and analyzed on IBM SPSS Statistics version 20, with descriptive statistics, independent-samples t test, Mann-Whitney U test and Kruskal-Wallis test. Average age of the participants is 22.19±4.17 (min:18-max:44) and average length of marriage is 6.21±5.48 (min:1-max:25). It is found that 33.3% of puerperant women is primary school graduate, 86.1% of them is housewife, 66.7% of them has elementary family and 76.4% of them has intended pregnancy. Postpartum Self Evaluation Questionnaire means score of 154.82±27.43 was found. Women who were high school or university graduates (p<0.01), employed (p<0.05), living in families (p<0.05), having high or good income levels (p<0.01), social security (p<0.01), willingly pregnant (p<0.01) and take-in information about the pregnancy (p<0.01) were found to be more compatible. As a result of the research, it has been found that the adaptation to Motherhood of Women at Postpartum Period is intermediate. In our study, it was shown that the sociodemographic and obstetric attributes have roles determining the adaptation to Motherhood of Women at Postpartum Period. Adaptation to motherhood of women’s is affected by many variables and given perinatal care is a great importance in ensuring compliance. All health care professionals who serve pregnant and puerperal women with caring for their involvement in the psychosocial as well as physical care may be required.